2007
DOI: 10.1128/jvi.00480-06
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus Type 1 (HTLV-1) bZIP Protein Interacts with the Cellular Transcription Factor CREB To Inhibit HTLV-1 Transcription

Abstract: The complex human T-cell leukemia virus type 1 (HTLV-1) retrovirus encodes several proteins that are unique to the virus within its 3-end region. Among them, the viral transactivator Tax and posttranscriptional regulator Rex are well characterized, and both positively regulate HTLV-1 viral expression. Less is known about the other regulatory proteins encoded in this region of the provirus, including the recently discovered HBZ protein. HBZ has been shown to negatively regulate basal and Tax-dependent HTLV-1 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
178
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(193 citation statements)
references
References 59 publications
11
178
1
3
Order By: Relevance
“…HBZ is a potent suppressor of Tax-mediated virus-gene transcription by interacting with activating transcription factor/cAMP responsive element-binding protein (CREB) and CREB-binding protien/p300 on the 5Ј-LTR promoter. 24,34,35 The HBZ role in the tightly regulated pattern of HTLV-1-gene expression also is suggested by HBZ repression of Gag-p19 synthesis in stable virus-producing cell clones. 36 Kinetic study of gene expressions in cells transiently transfected with the HTLV-1-provirus plasmid and in newly infected PBMCs showed that Gag/Pol, Tax/Rex, and Env mRNA are detected first and at their highest levels, whereas HBZ transcription was significantly lower and peaked later.…”
Section: Discussionmentioning
confidence: 99%
“…HBZ is a potent suppressor of Tax-mediated virus-gene transcription by interacting with activating transcription factor/cAMP responsive element-binding protein (CREB) and CREB-binding protien/p300 on the 5Ј-LTR promoter. 24,34,35 The HBZ role in the tightly regulated pattern of HTLV-1-gene expression also is suggested by HBZ repression of Gag-p19 synthesis in stable virus-producing cell clones. 36 Kinetic study of gene expressions in cells transiently transfected with the HTLV-1-provirus plasmid and in newly infected PBMCs showed that Gag/Pol, Tax/Rex, and Env mRNA are detected first and at their highest levels, whereas HBZ transcription was significantly lower and peaked later.…”
Section: Discussionmentioning
confidence: 99%
“…Cette famille comprend des facteurs de transcription capables de s'homodimériser ou de s'hétérodimériser via leur domaine ZIP. Alors que HBZ est incapable de s'homodimériser, il peut former in vivo des dimères avec des membres de la famille ATF/CREB et Jun (Figure 2) [9,[17][18][19][20][21]. En outre, grâce à son domaine d'activation, HBZ interagit aussi avec les cofacteurs transcriptionnels CBP/p300 [22].…”
Section: Hbz Déjoue Le Contrôle Immunitaireunclassified
“…Il est frappant de constater que HBZ cible les facteurs nucléaires qui sont impliqués dans le contrôle de la transcription virale Tax-dépendante (Figure 1). En fait, nous avons pu démontrer que HBZ régule négativement la transcription des autres gènes viraux en inhibant l'association de Tax avec CREB sur le promoteur du LTR 5' et en empêchant le recrutement de CBP/p300 sur ce même promoteur (Figure 3) [21,22]. …”
Section: Hbz Déjoue Le Contrôle Immunitaireunclassified
“…In HTLV-1 infected cells, Tax expression is negatively regulated by Rex, p30, and a newly discovered HTLV-1 basic leucine zipper (HBZ) factor encoded by an anti-sense mRNA transcribed from the 3' end of the proviral DNA (5,18,103,168). Despite the role of Tax in cell transformation and leukemogenesis, the leukemic cells of approximately 60% of ATL patients do not express tax transcript.…”
Section: Overview Of Htlv Taxmentioning
confidence: 99%